ANALISIS TINGKAT STRES KERJA TENAGA KESEHATAN PERIODE KABUT ASAP DI KOTA PEKANBARU TAHUN 2015 - Ibnu Affan; Zulfan Saam; Riki Sukiandra (Program Pascasarjana Universitas Riau, 2018)
Pekanbaru is one of the cities in Indonesia who has a negative impact on haze. The Government made efforts through blackouts water bomb and holiday of public service, except for police, health and fire suppression. Health sector is one of the sectors mostaffected in these policies. Some of the officers claimed to experience work stress because they worked in excess situations. This research aims to determine the periods of smog index parameters based on the standards of air pollution, the number of cases of respiratory and other diseases cases arising during the smog in Pekanbaru and analyze stress levels health work force aperiod of smog in the city Pekanbaru in 2015. This research used a qualitative approach to survey methods. The results showed that the period of fog happens in September and October, based on the parameters of the ranges in air pollution standards index on number 838 and categorized is very dangerous because it is above the range >400 the number of cases of respiratory and other diseases cases arising during the smog in the city of Pekanbaru. For the case of respiratory amounted to 2,462 cases. As for other diseases such as skin irritation amounted to 56 cases, eye irritation 37 cases, asthma 40 cases, pneumonia 56 cases and died 1 case. While the economic loss at the time of the occurrence of the smog periods which give rise to cases of respiratory illness and other diseases is Rp.518,158,880. Stress level health workforce a period of smog in the city of Pekanbar in 2015 is at a high category.